Zolgensma: The Costliest Drug In SMA – A Review (International Journal of Food and Nutritional Sciences, 2022)
Zolgensma stands as a pioneering gene therapy developed to address the complex challenges of Spinal Muscular Atrophy (SMA), a debilitating neuromuscular disorder. This abstract embarks on a comprehensive exploration of Zolgensma, delving into its mechanism of action, administration, approved indications, and potential adverse effects. What sets this analysis apart is the integration of advanced machine learning techniques, providing a data-driven assessment of Zolgensma's transformative impact on SMA treatment. The utilization of machine learning unravels new dimensions of efficacy and safety, offering a deeper understanding of this groundbreaking therapy.